Impact of Economic Growth, Minimum Wage, Labor Force Participation Rate, and Population Size on the Open Unemployment - Rusydan, Raden Muhammad; Wijaya, Riko Setya (Journal of Business Management and Economic Development, 2024)
Unemployment is a complex economic issue where individuals capable and willing to work cannot find suitable employment. This study examines the impact of economic growth, minimum wage, labor force participation rate (LFPR), and population size on the open unemployment rate (OUR) in Sidoarjo Regency. Using secondary time series data from 2009 to 2023, a descriptive quantitative approach with multiple linear regression analysis was employed, processed with SPSS 25 software. The findings indicate that, simultaneously, all variables significantly influence the open unemployment rate (OUR). Specifically, economic growth shows a negative but insignificant effect, minimum wage has a positive significant effect, labor force participation rate (LFPR) exhibits a negative but insignificant effect, and population size demonstrates a negative significant effect. This study provides insights into the dynamics influencing unemployment in Sidoarjo Regency, highlighting the critical roles of minimum wage and population size in shaping the employment landscape. Understanding these factors can help policymakers develop strategies to reduce unemployment and promote economic stability.